2020
DOI: 10.3390/ijms21072329
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Interference–Potential Application in Retinal Disease

Abstract: The treatment of dominantly inherited retinal diseases requires silencing of the pathogenic allele. RNA interference to suppress gene expression suffers from wide-spread off-target effects, while CRISPR-mediated gene disruption creates permanent changes in the genome. CRISPR interference uses a catalytically inactive ‘dead’ Cas9 directed by a guide RNA to block transcription of chosen genes without disrupting the DNA. It is highly specific and potentially reversible, increasing its safety profile as a therapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…The situation is even better for CRISPRi due to the very mechanism of action. The efficient inhibition of transcription requires long-term and high-affinity interaction between 17-20 nucleotide guide sequence and target DNA and therefore mismatch tolerance is low and the number of off-targets – negligible (Gilbert et al, 2014; Peddle, Fry, McClements, & MacLaren, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The situation is even better for CRISPRi due to the very mechanism of action. The efficient inhibition of transcription requires long-term and high-affinity interaction between 17-20 nucleotide guide sequence and target DNA and therefore mismatch tolerance is low and the number of off-targets – negligible (Gilbert et al, 2014; Peddle, Fry, McClements, & MacLaren, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to gene editing, CRISPR-Cas9 can be used for transcriptional regulation, in which catalytically inactivated "dead" Cas9 (dCas9) is fused to transcriptional effectors to repress genes directly (termed CRISPR interference or CRISPRi) or modified to act as a functional transcriptional activator (CRISPRa) 27 (Fig.1D). Multiple groups have shown that the mere binding of dCas9 to promoters and other regulatory regions can repress transcription by sterically hindering the RNA polymerase machinery 27 .…”
Section: Epigenetic Editingmentioning
confidence: 99%
“…In addition to gene editing, CRISPR-Cas9 can be used for transcriptional regulation, in which catalytically inactivated "dead" Cas9 (dCas9) is fused to transcriptional effectors to repress genes directly (termed CRISPR interference or CRISPRi) or modified to act as a functional transcriptional activator (CRISPRa) 27 (Fig.1D). Multiple groups have shown that the mere binding of dCas9 to promoters and other regulatory regions can repress transcription by sterically hindering the RNA polymerase machinery 27 . Nevertheless, the repressive capacity of the system is vastly improved when dCas9 is linked to a transcriptional repressor domain 28 For example, CRISPR-mediated epigenome editing may present a novel approach for robust and long-term suppression of vascular endothelial growth factor (VEGF-A) and reversal of the AMD-related phenotype (Table 1) 30 .…”
Section: Epigenetic Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRISPR-Cas9 technique relies on the endonuclease Cas9 to generate double-stranded breaks (DSBs) at a specific site of the genome with the subsequent repair of the induced breaks by the endogenous DSB repair machinery. Additionally, Cas9 lacking endonuclease activity can be used to selectively perturb genome expression by blocking transcription [2,3]. Repair of Cas9-induced DSBs takes place either by non-homologous end-joining (NHEJ) which is available in all cell cycle phases or by homologous recombination (HR).…”
Section: Introductionmentioning
confidence: 99%